Prediction of treatment response in head and neck carcinomas using IVIM-DWI: evaluation of lymph node metastasis - Hauser, Thomas; Essig, Marco; Jensen, Alexandra; Laun, Frederik B.; Münter, Marc; Maier-Hein, Klaus H.; Stieltjes, Bram (European journal of radiology, 2014)
Purpose - To obtain diffusion and microperfusion measures in lymph node metastases of head and neck squamous cell carcinomas (HNSCC) using intravoxel incoherent motion (IVIM) imaging. The obtained IVIM parameters were used to characterize lymph nodes in the staging phase and longitudinal follow-up was performed to evaluate the potential predictive value of these parameters considering therapy response. - Methods - Fifteen patients with lymph node metastases of histologically confirmed locally advanced HNSCC were examined using diffusion weighted imaging (DWI) before a nonsurgical organ preserving therapy. DWI imaging was performed at 3T using eight different b-values ranging from 0 to 800s/mm2. Using the IVIM-approach, the perfusion fraction f and the diffusion coefficient D were extracted using a biexponential fit. A follow-up period of 13.5 months was available for all patients. One patient with a macroscopically necrotic lymph node was excluded from analyses. A region of interest (ROI)-analysis was performed in all patients. - Results - Locoregional failure (LRF) was present in 3 of 15 patients within 13.5 months follow-up. The initial f-value was significantly higher (p=0.01) in patients with LRF (14.5±0.6% vs. 7.7±2.6%) compared to patients with locoregional control (LRC). The initial diffusion coefficient D did not differ significantly (p=0.30) between the two groups (0.97±0.15×10−3mm2/s vs. 0.88±0.13×10−3mm2/s). - Conclusions - Our results indicate that a high initial perfusion fraction f in lymph nodes may predict poor treatment response in patients with HNSCC due to locoregional failure.